The Speech Act of Thanking in Shakespeare: The Case of Romeo and Juliet and All’s Well that Ends Well - Chahra Beloufa (Universitas Ahmad Dahlan, 2022)
Shakespeare’s written words are not innocent. Many individual words from his dramatic texts can be “obscure or impenetrable”. They are not only meant to embellish the scene and the context, yet their elaboration is aimed to set up meaning and effect. In this part, we will analyze and look at how this utterance operates in characters’ dialogues. We will try to highlight Shakespeare conventionalized thank you, which can be not only a sign of gratitude but a complex emotion that adds to the dramatic situation. In the construction of Shakespeare's dialogues in the plays, many linguistic features are omnipresent and do serve a variety of functions. From a linguistic perspective, thanking is a conversational routine such as advising, requesting and complementing, yet in the use of thanking expressions, there is genuine artistry that Shakespeare wittingly invented. Some words carry risks when negotiating actions. We might think primarily of insults, criticisms and curses. These negative speech acts are not the only damaging and threatening in speech, there is also thanksgiving, which can be regarded as an element bearing risks. The present study focuses on the speech act of thanking in the Shakespearean corpus. The word